PHARMACEUTICAL STANDARDIZATION OF JATIPHALADYA VATI - Chand Verma, *Kailash; Mohan Rao, G. Rama (International Journal of Ayurveda and Pharma Research, 2016)
Standardization is the process of developing and agreeing upon technical standards. A standard is a document that establishes uniform engineering or technical specifications, criteria, methods, processes or practices. Many drugs are described in Ayurvedic classical texts for the treatment of various disorders. Jatiphaladya Vati is one such Kharaliya Rasayana mentioned in Rasendra Saara Samgraha, indicated in Arshas (Haemorrhoids). Jatiphala (Myristica fragrans Houtt.), Lavanga (Syzygium aromaticum), Pippali (Piper longum), Saindhava lavana (Rock salt), Shunthi (Zingiber officinale Roxb), Dhattura beeja (Datura metel Linn.), Hingula (Cinnabar) and Tankana (Borax) are the main ingredients. Shodhana (Purification), Churna nirmana (Preparation of powder), Bhavana (Soaking with liquid and triturating till drying) and Mardana (Trituration) are the important steps involved in preparation of Jatiphaladya Vati. Shodhana of Hingula, Tankana and Dhattura beeja was carried out by classical method to remove the impurities. Churna of all above ingredients were prepared by subjecting it to grinding in Khalwa yantra and filtering through cloth. All ingredients were mixed properly to make homogenous mixture; later on it was triturated with Nimbu swarasa to obtain 250 mg tablets (brick red in colour) in tablet compression machine. The present study has been planned to standardize the method of preparation of an important Herbo-mineral formulation i.e. Jatiphaladya Vati.